α-tubulin detyrosination fine-tunes kinetochore-microtubule attachments - Hugo Girão; Joana Macário-Monteiro; Ana C. Figueiredo; Ricardo Silva e Sousa; Elena Doria; Vladimir Demidov; Hugo Osório; Ariana Jacome; Patrick Meraldi; Ekaterina L. Grishchuk; Helder Maiato (Nature Communications)
Abstract Post-translational cycles of α-tubulin detyrosination and tyrosination generate microtubule diversity, the cellular functions of which remain largely unknown. Here we show that α-tubulin detyrosination regulates kinetochore-microtubule attachments to ensure normal chromosome oscillations and timely anaphase onset during mitosis. Remarkably, detyrosinated α-tubulin levels near kinetochore microtubule plus-ends depend on the direction of chromosome motion during metaphase. Proteomic analyses unveil that the KNL-1/MIS12/NDC80 (KMN) network that forms the core microtubule-binding site at kinetochores and the microtubule-rescue protein CLASP2 are enriched on tyrosinated and detyrosinated microtubules during mitosis, respectively. α-tubulin detyrosination enhances CLASP2 binding and NDC80 complex diffusion along the microtubule lattice in vitro. Rescue experiments overexpressing NDC80, including variants with slower microtubule diffusion, suggest a functional interplay with α-tubulin detyrosination for the establishment of a labile kinetochore-microtubule interface. These results offer a mechanistic explanation for how different detyrosinated α-tubulin levels near kinetochore microtubule plus-ends fine-tune load-bearing attachments to both growing and shrinking microtubules.